INTERKONEKSI MATEMATIKA DENGAN SURAH AL-KAHF AYAT KE-22 PADA AKTIVITAS BELAJAR SISWA MA DARUL ULUM KUBU RAYA - Bahrianto Bahrianto; Ade Mirza; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractMA Darul Ulum is a private school with a Tarbiah background where they get general lessons like students in general and in addition they also learn to memorize the Qur'an after studying from morning to afternoon, and in the afternoon until evening they carry out again. the same activity. Then in the process of student learning activities in the class, students should always connect mathematics with the Al-Qur'an so that students know that mathematics lessons that are often studied can be linked to the Al-Quran, especially SurahAl-Kahf verse 22. In this study, the method used is the connecting method designed into the Learning Implementation Design and after that it can be used by the teacher in carrying out the learning process obtained from the results of the implementation of the 22nd verse of the Al-Kahf chapter. The results in this study are the results of the implementation of the Al-Kahf surah which can be used in a learning design that uses the connecting method. Then in the implementation results obtained, there are core competencies from the first to the fourth which can be used in the Learning Design. For the conclusion itself, that is in the Al-Qur'an, especially Surah Al-Kahf verse 22, there are implementation results that can be used in the implementation of learning designed in the Learning Implementation Plan.Keywords : Interconnection, Mathematics, Learning Activities